The Roman Army in Jordan - Kennedy, David (Council for British Research in the Levant, 2004)
This is an updated and revised second edition of a handbook originally prepared for the XVIIIth International Congress of Roman Frontier Studies in Amman, Jordan in 2000 - a reflection of the growing importance of Roman studies in Jordan in recent years. In Part A, there are chapters on geography and environment, the Romans in Jordan and the Roman army there. In Part B there are 15 chapters surveying, region by region, the evidence for forts, towers, roads, literary texts, inscriptions and excavation around the entire country, ending with a chapter on the immediately adjacent parts of Roman Arabia that now lie in Syria, Saudi Arabia, Egypt and Israel. The book is profusely illustrated throughout and has many aerial views including 20 full-page photographs in colour.